Actual and Potential Gender-Fair Language Use: The Role of Language Competence and the Motivation to Use Accurate Language. (March 2014) - Kuhn, Elisabeth A.; Gabriel, Ute
In two paper-and-pencil studies on university students and trainees, we studied how general language competence and the motivation to use accurate language are linked to people's actual and potential gender-fair language use. Overall, participants' actual gender-fair language use was lower than their potential. The higher the participants' language competence, the higher their potential. Trainees' actual gender-fair language use was predicted by the interaction of language competence and motivation to use accurate language, those with relatively high language competence used less gender-fair language the higher their motivation to use accurate language was.